IMPLIKASI PUTUSAN MAHKAMAH KONSITUSI NOMOR 18/PUU-XVII/2019 TERHADAP PELAKSANAAN EKSEKUSI LEMBAGA JAMINAN - Eko Surya Prasetyo (Refleksi Hukum: Jurnal Ilmu Hukum, 2020)
The object of fiduciary security represents how important the principle of trust of the creditor is. Under the Fiduciary Law, creditors own rights to sell fiduciary collateral objects if the debtor is in breach of contract. Unfortunately, the Constitutional Court Decision No. 18/PUU-XVII/2019 reduced this right by granting the terms of the agreement of breach of contract and the debtor’s willingness to surrender the object of collateral. This paper reviewed the Decision highlighting material rights and their implications for the insurance institution. A normative juridical method using a statutory and conceptual approach was applied to conclude that the Decision is incompatible with the principle of material rights, especially the principle of droit de suite, droit de preference, and separate executive. It affects the time, cost, and the addition of new burdens in the execution of the collateral object execution. As a long-term recommendation, legislators need to amend the Fiduciary Law by affirming the executive power in fiduciary guarantees. Additionally, a change in the agreement deed clause and an effort to optimize the simple lawsuit mechanism are needed as a short-term recommendation.